A Huge Para-pharyngeal Mass: Excision through Trans-cervical Approach - Islam MA; Mohammad T; Lutfur ASM; Chowdhury NH; Milki FU (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
Para-Pharyngeal Space (PPS) is an inverted cone-shaped potential space that extends from the hyoid bone to the base of the skull. It is filled with fat and areolar tissue lie laterally on either sides of pharynx; and is bounded and subdivided by various condensations of fascia. Tumors, although rare less than1% of head neck neoplasm can arise from any structures of this space. Mostly they are benign 70-80% and 20-30% are malignant. Salivary gland tumor, particularly deep lobe parotid constitutes more than 80%. Imaging studies are invaluable to define the site of origin, extension, relationship to the great vessels of the neck and other neurovascular structures. Surgery is the mainstay of treatment. Several approaches have been discussed in the text books. We present a case of a huge para-pharyngeal space tumor that was excised completely through trans-cervical approach without any morbidly.